2016
DOI: 10.1200/jco.2016.66.9549
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organizational Characteristics on Outcomes and Resource Use in Patients With Cancer Admitted to Intensive Care Units

Abstract: Organizational aspects, namely the implementation of protocols and presence of clinical pharmacists in the ICU, and close collaboration between oncologists and ICU teams are targets to improve mortality and resource use in critically ill patients with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 27 publications
5
69
1
7
Order By: Relevance
“…Of those, 51 were in general hospitals and 19 were in cancer centers. The authors found that the presence of clinical pharmacists in the ICU, presence of ICU protocols, and daily meetings between oncologists and intensivists were associated with lower hospital mortality even after adjustment for hospital case volume (21). Protocols and daily meetings were also associated with more efficient resource utilization.…”
Section: Do Patients In Icus At Cancer Centers Perform Better Than Thmentioning
confidence: 90%
See 2 more Smart Citations
“…Of those, 51 were in general hospitals and 19 were in cancer centers. The authors found that the presence of clinical pharmacists in the ICU, presence of ICU protocols, and daily meetings between oncologists and intensivists were associated with lower hospital mortality even after adjustment for hospital case volume (21). Protocols and daily meetings were also associated with more efficient resource utilization.…”
Section: Do Patients In Icus At Cancer Centers Perform Better Than Thmentioning
confidence: 90%
“…The use of protocols co-developed by oncologists and intensivists may be the way to bridge the knowledge gap between medical specialties and improve outcomes for cancer patients in a general ICU while utilizing an existing infrastructure of high intensity staffing. Soares et al did not see improved outcomes with cancer specific protocols (21). Perhaps this is due to the number of or the specific protocols used.…”
Section: Do Patients In Icus At Cancer Centers Perform Better Than Thmentioning
confidence: 95%
See 1 more Smart Citation
“…After demonstrating organizational factors associated with improved outcome in critically ill cancer patients (namely presence of clinical pharmacist, daily meeting with oncologist and implemented clinical protocols) [1], Soares et al demonstrated an association between liberal visiting policies for family members and implemented processes to improve communication with families in units with higher performance as assessed by standardized mortality ratio or resource use as assessed by standardized resource use [14].…”
Section: Treatmentsmentioning
confidence: 99%
“…In this context, immunocompromised patients are a special population requiring specific knowledge, management and attention from the staff. Immunocompromised patients are being increasingly admitted to intensive care units (ICU), requiring complex and ideally multidisciplinary management [1]. Here, we summarize the most important recently published papers in this field.…”
Section: Introductionmentioning
confidence: 99%